Effect of unconventional filters on uniformity, sensitivity and linearity of an imaging system in SPECT - Sayed, Inayatullah Shah; Ahmad, Zakaria; Yee, Fong Shu (Springer Netherlands, 2004)
The prime objective of the SPECT imaging is to provide the best possible diagnostic service to the patient's. For achieving this. It is vital to tset the performance parameters of the imaging system. Such as, spatial resolution, centre of rotation, uniformity, linearity and sensitivity. In this work, the performance parameters of a Toshiba gamma camera GCA-901A/HG were investigated such as; uniformity, linearity and sensitivity with the use of unconventional (material) filters (Al 0.2mm and Cu 0.125mm thick sheets). Which were mounted on the face of collimator either LEGP or LEHR seperately. SPECT data were acquired by imaging a cylindrical phantom (carlson) with the linearity insert by loading Tc-99m radionuclide. Standard energy window (20% at 140 keV) was adjusted. Our results show that the improvement in uniformity and linearity over the reduction in system sensitivity. It is concluded that, this may have some advantages in terms of enhancement in image quality.